Usual blood pressure, peripheral arterial disease, and vascular risk: cohort study of 4.2 million adults. (29th September 2015) - Emdin, Connor A; Anderson, Simon G; Callender, Thomas; Conrad, Nathalie; Salimi-Khorshidi, Gholamreza; Mohseni, Hamid; Woodward, Mark; Rahimi, Kazem
Abstract : Objectives To determine the subgroup specific associations between usual blood pressure and risk of peripheral arterial disease, and to examine the relation between peripheral arterial disease and a range of other types of vascular disease in a large contemporary cohort. Design Cohort study. Setting Linked electronic health records from 1990 to 2013 in the United Kingdom. Participants 4 222 459 people aged 30-90 years, registered at a primary care practice for at least one year and with a blood pressure measurement. Main outcome measures Time to first diagnosis of new onset peripheral arterial disease and time to first diagnosis of 12 different vascular events. Results A 20 mm Hg higher than usual systolic blood pressure was associated with a 63% higher risk of peripheral arterial disease (hazard ratio 1.63, 95% confidence interval 1.59 to 1.66). The strength of the association declined with increasing age and body mass index (P<0.001 for interaction) but was not modified by sex or smoking status. Peripheral arterial disease was associated with an increased risk of 11 different vascular events, including ischaemic heart disease (1.68, 1.58 to 1.79), heart failure (1.63, 1.52 to 1.75), aortic aneurysm (2.10, 1.79 to 2.45), and chronic kidney disease (1.31, 1.25 to 1.38), but not haemorrhagic stroke. The most common initial vascular event among those with peripheral arterial disease was chronic kidney disease (24.4% of initial events), followed by ischaemic heart disease (18.5% of initial events), heart failure (14.7%), and atrial fibrillation (13.2%). Overall estimates from this cohort were consistent with those derived from traditional studies when we pooled the findings in two meta-analyses. Conclusions Raised blood pressure is a strong risk factor for peripheral arterial disease in a range of patient subgroups. Furthermore, clinicians should be aware that those with established peripheral arterial disease are at an increased risk of a range of other vascular events, including chronic kidney disease, ischaemic heart disease, heart failure, atrial fibrillation, and stroke.